Adaptive Second-Order Synchronization of Two Heterogeneous Nonlinear Coupled Networks. (12th October 2015) - Liu, Bo; Li, Shuang; Tang, Xuhui
Abstract : This paper investigates the second-order synchronization of two heterogeneous nonlinear coupled networks by introducing controller and adaptive laws. Based on Lyapunov stability properties and LaSalle invariance principle, it is proved that the position and the velocity of two heterogeneous nonlinear coupled networks are asymptotically stable. Finally, some numerical simulations are presented to verify the analytical results.